Pengaruh Pemberian Konseling Melalui Media Leaflet terhadap Pengetahuan tentang Penghitungan Gerakan Janin pada Primigravida - Fadtum syamlan; Arum Meiranny (Midwifery Care Journal, 2026)
Fetal movement monitoring is a vital indicator of fetal health in uterus. Low knowledge among pregnant women, especially primigravida, regarding fetal movement counting can increase the risk of pregnancy complications and fetal death. This study aimed to determine the effect of counseling using leaflet media on knowledge of fetal movement counting among primigravida at PMB Fattum Tamim Syamlan Krapyak Pekalongan. This study utilized a quasi-experimental design with a pre-test and post-test approach and a control group. A total of 70 second-trimester primigravida mothers were selected through purposive sampling and divided into an intervention group (n=35) and a control group (n=35). The intervention group received counseling using leaflet media about fetal movement counting, while the control group received no intervention. Data were collected using a knowledge questionnaire and analyzed using the Chi-Square test. The findings revealed a significant increase in knowledge in the intervention group, from 17.1% in the good category during pre-test to 80.0% during post-test. Meanwhile, the control group remained predominantly in the poor knowledge category (68.6%). The Chi-Square statistical test showed a p-value of 0.000 (p < 0.05), indicating a significant effect of counseling using leaflet media on fetal movement counting knowledge among primigravida. Counseling using leaflet media is proven effective in improving primigravida knowledge about fetal movement counting. Leaflets are recommended as an educational medium in antenatal care services to increase pregnant women's awareness of fetal well-being monitoring